THE IMPACT OF USING INFORMATION AND COMMUNICATION TECHNOLOGY ON STUDENTS' CRITICAL THINKING SKILLS IN ELEMENTARY SCHOOLS - Putu Satya Narayanti; Muhammad Lutfi (Adisam Publisher, 2026)
This research examines the impact of the use of Information and Communication Technology (ICT) on the development of students' critical thinking skills in elementary schools through a literature review. ICT is recognized as having the potential to increase student engagement, motivation and analytical abilities. This literature review examines various empirical research and theories that discuss the contribution of ICT in the context of basic education. The results of the study show that effective ICT integration can improve critical thinking skills, as long as it is supported by relevant quality content, interactive teaching methods, and teacher competence in utilizing technology optimally. Several approaches such as project-based learning and collaborative discussions have proven to be more effective in developing critical thinking competencies than conventional methods. In addition, continuous training for teachers to master and apply ICT strategically in learning was found to be an important factor supporting this success. This study highlights the need for integrative strategies and institutional support to maximize the potential of ICT in the development of students' critical thinking skills at the primary school level.